Expression of CD123 in B-Acute Lymphoblastic Leukemia as a Predictor of BCR/ABL rearrangement and Disease Relapse - Birva Nimit Raiya (Basic & Clinical Cancer Research)
Introduction: CD123 is the alpha chain of the interleukin 3 receptor (IL-3R) and normally expressed on hematopoietic progenitor cells, monocytes, B lymphocytes and endothelial cells. Leukemic stem cells can be detected using CD123, and its usefulness for measuring residual disease and potential involvement in disease relapse is being evaluated. It also regulates the growth, proliferation, survival, and differentiation of hematopoietic cells, along with immunity and inflammatory response.